THE EFFECT OF WORK LIFE BALANCE AND HYBRID WORKING SYSTEM ON THE PRODUCTIVITY OF THE MARKETING DIVISION AT PT. PIM - Likdanawati; Hamdiah; Muttaqien (RADJA PUBLIKA, 2025)
This study aims to evaluate the influence of Work Life Balance and Hybrid Working System on the productivity of employees in the Marketing Division at PT. PIM. The research adopts a quantitative approach with a causal-comparative method. The entire population consists of employees in the Marketing Division, with samples selected using purposive sampling based on at least one year of work experience and prior participation in a hybrid working system. Data analysis employs the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method, considered suitable for assessing relationships among latent variables and indicators in cases of non-normal data and relatively small sample sizes. The results indicate that Work Life Balance has a positive and significant effect on employee productivity; in other words, the better the work life balance experienced by employees, the higher their productivity. In addition, the Hybrid Working System also shows a positive and significant effect on productivity. An optimally implemented hybrid system provides flexibility in managing work time and location, thereby increasing motivation, reducing fatigue, and driving employee productivity.